Życie człowieka w semiotyce koloru na przykładzie języka polskiego i rosyjskiego (część II) - Narloch, Andrzej (Acta Polono-Ruthenica, 2019)
In the contemporary linguistic research, the colour system occupies a special position. Today’s culture space is supersaturated with colours, which are important semiotic components of human functioning and their relationships with other people. This paper attempts to describe colour semiotics from the point of view of the human development period. The author tries to determine whether colours can also determine the age frame of a person. First, the relationship between colours and time is analysed. The suggested description of the stages of life through the colour spectrum allows answering the question of how the respective stages of human life are determined by the colours assigned to them by the culture.